Peer Conformity and Students’ Misbehaviour: Religiusity As Moderation - Nur Saqinah Galugu; Umrah Qhairunnisa; Andi Arisal (EduPsyCouns: Journal of Education, Psychology and Counseling, 2023)
Abstract: Misbehavior is negative behavior displayed by students at school. This deviant behavior is increasingly prevalent among students and is influenced by many factors, both internal and external factors. This study aims to examine the effect of peer conformity on misbehavior and also to examine the role of religiosity as a moderating variable. This research was conducted at SMA Negeri 3 Palopo with 103 students as the subject. Data were collected using a questionnaire and distributed via google form. The analysis showed that there was a positive influence between conformity and misbehavior by 38.7%. After the moderating variable (religiosity) in the second regression equation, the R square value increases to 99.3% So it can be said that the existence of the religiusity variable as a moderating variable will be able to strengthen or increase the influence of the conformity variable on the misbehavior variable, in other words the higher one's religiosity. the lower the tendency for a person to perform misbehavior which is influenced by confidence. Abstrak: Perilaku menyimpang merupakan perilaku negative yang ditampilakn oleh siswa di sekolah. Perilaku menyimpang tersebut semakin marak di kalangan siswa dan dipengaruhi oleh banyak factor baik factor internal maupun factor eksternal. Penelitian ini bertujuan untuk menguji pengaruh konformitas teman sebaya terhadap perilaku menyimpang dan juga menguji peran religiusitas sebagai variabel moderasi. Penelitian ini dilaksanakan di SMA Negeri 3 Palopo dengan jumlah subjek sebanyak 103 siswa. Data dikumpulkan menggunakan angket dan disebarkan melalui google form. Hasil analisis menunjukkan bahwa terdapat pengaruh positif antara konformitas terhadap perilaku menyimpang sebesar 38,7%. Setelah adanya variabel moderasi (religiusitas) pada persamaan regresi kedua, nilai R square tersebut meningkat menjadi 99,3% Sehingga dapat dikatakan bahwa keberadaan variabel religiusitas sebagai variabel moderasi akan dapat memperkuat atau meningkatkan pengaruh variabel konformitas terhadap variabel Perilaku Menyimpangdengan kata lain semakin tinggi religiusitas seseorang maka semakin rendah kecenderungan seseorang dalam melakukan perilaku menyimpang yang dipengaruhi oleh konfomitas